KRISIS KESANTUNAN BERBAHASA PADA KALANGAN KPOPERS DALAM APLIKASI X/ TWITTER: KAJIAN PRAGMATIK - Santi Amelia; Achmad Wahidy; Masnunah (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
The problem in this study is the Crisis of Language Civility Among Kpopers in the X / Twitter Application. This politeness crisis was studied to address the problem of decreasing the quality of polite language use, because people, especially young K-Pop fans, use less polite words as insert words used in everyday life when using social media. This study aims to determine and describe the crisis of language politeness among kpopers in the X / Twitter application. In this study, researchers used Leech's theory which consists of ten maxims of language politeness. The type of research used is a qualitative descriptive method. The source of data in this study is found on Kpopers in the X / Twitter application. The methods used to collect data are Listen, documentation, and record. Data analysis techniques use descriptive analytical techniques, then the data validity technique used is source triangulation. From the results of research on the crisis of language politeness in kpopers factories in the X / twitter application, 9 forms of language politeness maxims were found from 10 Leech language politeness maxims.